THE ROLE OF SELF-EFFICACY IN IMPROVING THE SELF-CONFIDENCE AND ABILITIES OF CHILD CLIENTS - Andre Manuella Pasaribu; Muhammad Ali Equatora (Universitas Nusa Cendana, 2026)
This study examines the issue of low self-efficacy and self-confidence among Children in Conflict with the Law during their rehabilitation at Pusat Pelayanan Sosial Griya Bina Karsa. The research aims to identify the role of self-efficacy in improving children’s confidence and abilities throughout the rehabilitation process. Using a qualitative case study approach, data were collected through in-depth interviews and observations involving child clients, community counselors, and social workers. The findings reveal that interventions such as skills training, non-formal education, and social support play a significant role in enhancing children’s self-efficacy. These efforts help improve their confidence, adaptability, and readiness to reintegrate into society while reducing the risk of reoffending. The development of self-efficacy occurs gradually through strengthening motivational, cognitive, and emotional aspects. These findings highlight that self-efficacy is a crucial foundation for building positive behavior and supporting successful social reintegration among children undergoing rehabilitation. Keywords: Self-Efficacy; Self-Confidence; Ability; Children in Conflict with the Law